Bis(4-aminopyridinium) bis(oxalato-κ(2) O,O′)cuprate(II) dihydrate - Pan, Zi-Cai (International Union of Crystallography, 2007)
The Cu(II) atom in the title salt, (C(5)H(7)N(2))(2)[Cu(C(2)O(4))(2)]·2H(2)O, is located on a center of inversion and is chelated by two oxalate groups in a square-planar coordination geometry. The cation, anion and water molecules interact through hydrogen bonds, forming a three-dimensional hydrogen-bonded network.